Hubungan Tekstur Sedimen dengan Kemelimpahan Larva Polycentropodidae (Trichoptera) di Waduk Sermo, Kulonprogo, Yogyakarta - Wibowo Nugroho Jati (Biota : Jurnal Ilmiah Ilmu-Ilmu Hayati, 2004)
A study on sediment texture to the abundance of Polycentropodidae’s larvae has been done in Sermo Water Reservoir, Kulonprogo, Yogyakarta. Samples have been taken in 3 rivers i.e. Ngrancah, Tegalrejo and Sidowayah. Four different depth were assessed i.e. 0 – 5 m, 5 – 10 m, 10 – 15m, and 15 – 20 m. Result showed that the larvae’s abaundance was hishest in Ngrancah river on depth of 0 – 5 m with 53 ind/m2 and lowest on Tegalrejo river on depth of 15 – 20 m with 3 ind/m2. The larvae’s abundance in every depth was characterized by sand texture and its depth.